2013
DOI: 10.1523/jneurosci.3338-13.2013
|View full text |Cite
|
Sign up to set email alerts
|

Extinction of Remotely Acquired Fear Depends on an Inhibitory NR2B/PKA Pathway in the Retrosplenial Cortex

Abstract: As memories age, their processing increasingly relies upon cortical rather than hippocampal circuits, but the adaptive significance and mechanisms of this shift are not fully understood. Here we investigated the behavioral features and cortical mechanisms underlying extinction of remotely versus recently acquired context fear in mice. Behaviorally, extinction and reinstatement were similar, but reextinction of remote fear was significantly faster, suggesting time-dependent engagement of mechanisms specific for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 50 publications
3
35
0
Order By: Relevance
“…However, more recent fear memories bound to the influence of fear incubation are more prone to failures of extinction retrieval that may include reinstatement, spontaneous recovery and renewal. Indeed, a recent study by Corcoran et al (2013) found that recently extinguished context fears are more prone to the effects of reinstatement than remotely extinguished contexts. Other studies examining the time-dependent effects of memory and extinction have focused on auditory fear extinction at shorter times scales from minutes to a few days (Myers et al 2006;Maren and Chang 2006).…”
Section: Discussionmentioning
confidence: 99%
“…However, more recent fear memories bound to the influence of fear incubation are more prone to failures of extinction retrieval that may include reinstatement, spontaneous recovery and renewal. Indeed, a recent study by Corcoran et al (2013) found that recently extinguished context fears are more prone to the effects of reinstatement than remotely extinguished contexts. Other studies examining the time-dependent effects of memory and extinction have focused on auditory fear extinction at shorter times scales from minutes to a few days (Myers et al 2006;Maren and Chang 2006).…”
Section: Discussionmentioning
confidence: 99%
“…It is wellestablished that CB1Rs play a pivotal role in memory extinction, at least in the amygdala and the hippocampus (Marsicano et al 2002;Chhatwal et al 2005;Pamplona et al 2006;Lutz 2007;De Oliveira Alvares et al 2008b). Recently, two important studies showed the involvement of the RSC in memory extinction (Corcoran et al 2013;Kwapis et al 2014). Here, we have shown that the cannabinoid system of the RSC is strongly engaged in this process.…”
mentioning
confidence: 99%
“…It is thought that memory retrieval initially relies upon hippocampal mechanisms, but over time comes to require a distributed network of cortical sites (Squire et al 2004). Additionally, retrieval of remote memories for contextual fear conditioning requires the activation of the cAMP-PKA-CREB signaling pathway in RSC, whereas recent retrieval does not (Corcoran et al 2013). RSC receives inputs from both hippocampus and cortical areas necessary for remote memory retrieval, such as anterior cingulate cortex (Frankland et al 2004); thus, M 2 and M 4 may become engaged and cAMP-dependent signaling comes online as memories age and cortical inputs to RSC begin to take precedence over hippocampal inputs.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that a remote drug-free test does not diminish the role of RSC in memory retrieval during a second test the following day (i.e., the "remote" memory is not made "recent" by the first drug-free remote memory test; Corcoran et al 2011). This single test is also not sufficient to cause extinction of the freezing response (Huh et al 2009;Corcoran et al 2013). Repeated-measures ANOVA indicated significant effects of day (F (1,15) ¼ 14.417, P ¼ 0.002) and drug (F (1,15) ¼ 12.445, P ¼ 0.003), and a significant day by drug interaction (F (1,15) ¼ 10.540, P ¼ 0.005).…”
Section: Retrieval Of Remotely Acquired Context Memories Requires Rscmentioning
confidence: 99%
See 1 more Smart Citation